STRATEGI BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM MENYALURKAN DANA ZAKAT, INFAK, SEDEKAH (ZIS) DI BIDANG PENDIDIKAN KECAMATAN SAMBAS KABUPATEN SAMBAS - EVA; Neli; Sulastri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This research is motivated by the Strategy of the National Zakat Amil Agency (BAZNAS) in channeling Zakat Infaq and Alms (ZIS) funds for education is very important for children to study at a higer level, but there are still many children who are less able to do so. Continuing education due to family economic factors. So that way BAZNAS created a superior program. This program focuses on school children who are less able to complete school. The National Zakat Amil Agency (BAZNAS) provides assistance in the form of school supplies that they need, starting from money, bags,pens,books, pencils and other school supplies. The aim of this research is to determine the strategy of the National Zakat Amil Agency (BAZNAS) in distributing zakat, infaq and alms funds in the education sector of Sambas District, Sambas Regency. Apart from that, it is also to find out what are the inhibiting factors in distributing zakat, infaq and alms funds in the education sector of Sambas District, Sambas Regency. This type of research is field research, using a qualitative descriptive approach. The data collection technique used was through observation interviews and documentation based on existing sources in the field related to this research. The results of this research conclude that BAZNAS strategy in distributing zakat, infaq and alms funds in the education sector in Sambas District has been running well, although sector in Sambas District has been running well, although it is not optimal. BAZNAS strategy in distributing zakat, infaq and alms funds in the education sector in Sambas District is to collaborate with schools. And institution related to the process of distributing ZIS funds in the education sector. There are 3 programs in the Sambas Regency BAZNAS program, namely education, health and house renovation programs. ZIS funds are collected by BAZNAS and distributed to 8 (eight) Asnaf, namely the Poor, Poor Amilin, Muallaf, Gharimin, Riqab, Fisabilillah and Ibnu Sabil. One form of responsibility is by channeling the zakat funds that have been collected to help reduce educational costs for people in need.